2001
DOI: 10.1007/bf03395393
|View full text |Cite
|
Sign up to set email alerts
|

Do Chimpanzees Have Expectations About Reward Presentation Following Correct Performance on Computerized Cognitive Testing?

Abstract: To investigate whether 2 chimpanzees had expectations regarding the outcome of their responses on a computerized task, food reward that typically was given for correct responses was withheld on some correctly completed trials. There were two types of these probe trials: those which the chimpanzees performed correctly on their own, and those during which the chimpanzees needed the experimenter's assistance to complete the trial correctly. For both chimpanzees, reward procurement behaviors directed toward the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The results indicated that the chimpanzees performed at a high level and showed the signature ratio effects seen in other experiments that require relative quantity judgments by these apes (e.g. Beran 2001, 2004; Beran & Beran 2004). …”
Section: Methodssupporting
confidence: 67%
See 3 more Smart Citations
“…The results indicated that the chimpanzees performed at a high level and showed the signature ratio effects seen in other experiments that require relative quantity judgments by these apes (e.g. Beran 2001, 2004; Beran & Beran 2004). …”
Section: Methodssupporting
confidence: 67%
“…Beran 2001, 2004, 2012; Beran & Beran 2004). In those tests, all items that were seen were relevant to the representations that the chimpanzees formed and used to choose between sets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations